Antihepatitis coverage B. health workers. Civil Hospital of Maracay. Girardot municipality. Aragua 2014 (Revista Venezolana de Salud Pública, 2018)
Hepatitis B infection is a public health problem, which according to the Pan American Health Organization, Venezuela has an intermediate prevalence (2.2 – 8 percent) and the highest associated factor is occupational exposure to sharp objects, therefore, international health agencies indicate vaccination. This issue prompted the research that determined the vaccination coverage against hepatitis B in workers at "Dr. Abbot Ephraim " Outpatient Clinic and Girardot Aragua State
Keywords: healthworkers; vaccination coverage; vaccination scheme; Hepatitis B.